Genomic Landscape and Phenotypic Assessment of Cronobacter sakazakii Isolated From Raw Material, Environment, and Production Facilities in Powdered Infant Formula Factories in China - Gan, Xin; Li, Menghan; Yan, Shaofei; Wang, Xiaofei; Wang, Wei; Li, Fengqin (Frontiers in Microbiology, 2021)
Cronobacter is a foodborne pathogen associated with severe infections and high mortality in neonates. The bacterium may also cause gastroenteritis, septicemia, and urinary tract and wound infectious in adults. A total of 15 Cronobacter isolates collected from 617 raw materials and environment samples from Powdered Infant Formula manufacturing factories during 2016 in Shaanxi, China, were analyzed for antimicrobial susceptibilities, species identification, biofilm formation and whole genome sequencing. The results showed that all 15 isolates were C. sakazakii, while the antimicrobial susceptibility test showed that all 15 C. sakazakii were pan susceptible. Most isolates were able to produce a weak biofilm and two isolates from soil samples produced a strong biofilm formation. All isolates were classified into seven STs including ST4, ST40, ST64, ST93, ST148, ST256, and ST494, with ST64 (4/15, 26.7%) being dominant, and most were clinically related. The isolates harbored at least 11 virulence genes and two plasmids, with one isolate being positive for all virulence genes. Phylogenetic and ANI analysis showed strong clustering by sequence types and isolates from different sources or regions had similar genomic background. The fact that isolates were obtained from raw materials and environment samples of PIF facilities shared a close phylogeny with one another suggests that cross contamination events may have occurred between the processing room and external environments, which may give rise to a recurring risk of a continuous contamination during production.